Acute Musculoskeletal Sports Injuries in School Age Children in Britain. Issue 8 (August 2021) - Mitchell, Piers D.; Pecheva, Mira; Modi, Nishil
Highlights: The greatest number of injuries were due to football, which is the most popular participation sport in Britain amongst children For the number of children who play it, rugby was responsible for a disproportionately large number of serious injuries and burden on the NHS. Many sports enjoyed by children had low likelihood of acute musculoskeletal injury, such as swimming, athletics, cricket, tennis and badminton We identify classic injuries associated with popular sports, such as finger hyperextension in ball sports Abstract: Objectives: To determine the relative number of acute musculoskeletal injuries sustained by children due to different sports in a region of the UK, and assess the burden upon the NHS, through a cross sectional study. Methods: Collection of data for every child aged 6-18 seen at the Peterborough City Hospital fracture clinic, whose sports injury was from 1 st September 2018 – 31 st August 2019 (1 school year; n=689). Data was gathered throughout the year by three children's orthopaedic surgeons, who consulted the clinic records, notes and x-rays of all children who had attended clinic. Results: Boys were 2.7 times more likely to sustain injury than girls. Children aged 6-9 had few injuries (mean 24 injuries each year group), 10-15 had a large number of injuries (mean 84), and 16-18 again had few injuries (mean 35). Football and rugby were responsible for the majority of injuries (61% between them), as well as the majority of physiotherapy appointments (72%). Sports with the highest likelihood that an injury will be sufficiently serious to require surgery were equestrian (42% of injuries required surgery), gymnastics (27%), ice skating (25%) and rugby (22%). Popular sports in which injuries were relatively rare include swimming, athletics, cricket, hockey, tennis and badminton. Conclusion: The sports that caused the most injuries were football and rugby. Considering relative participation in different sports, it is clear that rugby has a disproportionate number of musculoskeletal injuries in total, of severe injuries requiring surgery, and requiring rehab from physiotherapy.